L’assurance de responsabilité civile : caractéristiques et distinctions - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1982)
Progress whether scientific, industrial or economic together with a generally greater awareness of social justice has brought General Public Liability insurance to the forefront. In his exposé, Mr. Moreau examines not only the make-up of the two basic policy types, general and professional, and the various distinguishing features of each, but also why it is imperative professionals today ensure themselves this double coverage.